Meeting Of The Board Of Directors, Jan. 25, 1918 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
W. R. Ingalls made an oral address on the subject of the 27th Engineers, and it was resolved that notice of the needs of the Association of the 27th Engineers be communicated to the members through the Bulletin. Robert W. Hunt was appointed representative of the Institute on the Commission of Award of the Washington Medal of the Western Society of Engineers. The budget for the year 1918 was adopted. The report of the Library Committee for the year 1917 was accepted. An appropriation of $50 to the Treasurer's clerk was made. The appointment of the tellers made at the last meeting of the Board was confirmed.